New potential in the treatment of moderate to severe intrauterine adhesions: influencing factors for menstrual improvement - Zhang, Xin-Yue (Frontiers in Reproductive Health, 2025)
BackgroundThis article reviews the research progress in recent years on the influencing factors for menstrual improvement in patients with moderate to severe Intrauterine Adhesions. To improve the treatment effect, reduce the risk of re-adhesion, optimize the treatment plan, enhance patients' quality of life, and prevent infertility and miscarriage.ObjectiveIdentify the factors that may affect menstrual improvement in patients with moderate to severe Intrauterine Adhesions.MethodAn in-depth literature search was carried out on four databases to sort out the research results on the influencing factors of menstrual improvement in patients with moderate to severe Intrauterine Adhesions from 2014 to 2024.FindingsThe review incorporated 61 papers and found that the influencing factors for menstrual improvement in patients with moderate to severe Intrauterine Adhesions involve: (1) The development of the Müllerian duct and the levels of Anti-Müllerian Hormone. (2) The interaction and dynamic changes between Mesenchymal Stem Cells and the endocrine system. (3) The impact of hysteroscopic surgery on the endometrium and menstrual improvement, including the effects of the operation method, frequency of implementation, and postoperative management of hysteroscopic surgery. (4) The role of psychological factors.DiscussionThe results of this review highlight the factors influencing menstrual improvement in patients with moderate to severe Intrauterine Adhesions. However, the influencing factors of menstrual improvement are multifaceted and interrelated. Future research needs to further explore the interactions among these factors and how to optimize treatment plans to improve treatment outcomes.